METHOD OF JUSTIFICATION OF THE ESTIMATED COSTS FOR INFORMATION SECURITY BUDGET ORGANIZATIONS - Igor Mandritsa; Olga Mandritsa; Irina Solovyova; Vladimir Petrenko (Вестник Северо-Кавказского федерального университета)
The paper presents a new approach to substantiate the amount of expenses on information security, step-by-step algorithm offinding the balance between information security threats and the cost of protection. The stages of action offinding the probable effects of information threats on the security for the subject fiscal activities and their corresponding probable amounts on security. Presents the forecast calculation of levels of threats, and possible damages on the canals of threats of leaks. Presents the calculation of measures to improve information security.